ANALISIS PENERIMAAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DAN RETRIBUSI PERIZINAN TERTENTU SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA LHOKSEUMAWE - Muhammad Arif Saputra; Razif Razif; Wahyuddin Wahyuddin; Nurhasanah Nurhasanah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2022)
AbstractThis study examined the contribution of Customs Tax on Land and Building Rights (BPHTB) and certain licensing levies on Local Revenues of Lhokseumawe City in 2015-2019 and collected the data through interviews and documentation. The method used was a descriptive research method with a case study approach to present facts regarding the effectiveness and contribution of regional retribution revenues to Local revenues. The results indicated that the contribution rate of the Customs for Acquisition of Rights on Land and Buildings (BPHTB) to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very low category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The Effectiveness of Acquisition of Rights on Land and Buildings (BPHTB) on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The effectiveness level of certain licensing levies on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The factors causing those were the lack of public awareness and compliance with the mandatory retribution in fulfilling retribution obligations and the lack of local government performance in increasing regional levies. AbstractThis study examined the contribution of Customs Tax on Land and Building Rights (BPHTB) and certain licensing levies on Local Revenues of Lhokseumawe City in 2015-2019 and collected the data through interviews and documentation. The method used was a descriptive research method with a case study approach to present facts regarding the effectiveness and contribution of regional retribution revenues to Local revenues. The results indicated that the contribution rate of the Customs for Acquisition of Rights on Land and Buildings (BPHTB) to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very low category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The Effectiveness of Acquisition of Rights on Land and Buildings (BPHTB) on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The effectiveness level of certain licensing levies on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The factors causing those were the lack of public awareness and compliance with the mandatory retribution in fulfilling retribution obligations and the lack of local government performance in increasing regional levies. Keywords : Effectiveness, Contribution, Regional Retribution, Intensification, Extensification, andLocal Revenues.AbstractThis study examined the contribution of Customs Tax on Land and Building Rights (BPHTB) and certain licensing levies on Local Revenues of Lhokseumawe City in 2015-2019 and collected the data through interviews and documentation. The method used was a descriptive research method with a case study approach to present facts regarding the effectiveness and contribution of regional retribution revenues to Local revenues. The results indicated that the contribution rate of the Customs for Acquisition of Rights on Land and Buildings (BPHTB) to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very low category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The level of contribution of certain licensing levies to Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very less category. The Effectiveness of Acquisition of Rights on Land and Buildings (BPHTB) on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The effectiveness level of certain licensing levies on Local Revenues (PAD) of Lhokseumawe City in 2015-2019 was in the very effective category. The factors causing those were the lack of public awareness and compliance with the mandatory retribution in fulfilling retribution obligations and the lack of local government performance in increasing regional levies. Keywords : Effectiveness, Contribution, Regional Retribution, Intensification, Extensification, andLocal Revenues.